Innovation and the development of exportable supply in non-traditional goods: A longitudinal study in a Latin American economy (2017)
Purpose - This paper aims, first, to advance the current understanding about the impact of innovation in non-traditional exports, and, second, to provide insights about the structure of emergent economies often not regarded by traditional innovation and export theories. Design/methodology/approach - A longitudinal analysis using panel data based on Box Jenkins' theory was conducted, so to identify statistically significant variables on export performance, regarding expenditure on research, development and innovation (R and D + I) activities, ICT and specialized training and formation. Findings - This study suggests the need to design public policies aimed at stimulating innovation in potential export sectors, as a mechanism for competitive development and growth in emergent economies such as Colombia. Originality/value - The introduction of innovations in goods and services exports has become more important in economies, such as the Colombian ones, where globalization openness processes force to establish minimum competitiveness levels regarding the international standards. © 2017 Emerald Publishing Limited.